Nilai Pendidikan Karakter dalam Ilalat Masyarakat Ranah: Prespektif Thomas Lickona - Nur, Hidayatun; Rahyu, Sri; Octa Hadiyanti, Putri; Asnawi, Asnawi; Mukhlis, Muhammad; Ersalianda, Dilla; Reinov Ardi, Veronica (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
Ilalat is sometimes used and integrated in a series of traditional ceremonies. Ilalat or proverbs of the Ranah community have begun to fade in use in the digital era in communicating and interacting within their community. The purpose of this study is to examine the character education values proposed by Lickona contained in the ilalat of the Ranah community. In addition, this study aims to describe the use of Ilalat in society in the current digital era. The method used in this study is a descriptive qualitative method with a phenomenological strategy. Data collection was carried out through interviews with informants, observation and document study. Data analysis was carried out using interactive analysis. The character education values contained in the ilalat of the Ranah community are the values of self-control, respect, compassion, justice, responsibility, cooperation, courage, honesty, tolerance, mutual assistance, democracy, discipline, and humility. The most dominant character education value is prudence or self-control. The use of proverbs and sayings in the Ranah community in the digital era is still present in traditional ceremonies. This is because the Ranah community places great emphasis on polite language and manner of delivery. The use of proverbs in everyday communication and interactions has decreased and faded, as few people in the Ranah community can use proverbs.